Disputed meanings about child labour, its consequences, and interventions: discussions based on ethnographic research in Argentina - Rausky, María Eugenia (Third world thematics.)
Based on ethnographies with working children and their families in low-income neighbourhoods in Argentina, this article explores the experiences constructed around child labour, its meanings, and consequences, taking into account the locations and social relations in which it takes place. In doing so, it offers a nuanced reading of child labour that distances it from the dualistic thinking, deeply rooted in social sciences, in which, on the one hand, researchers conclude that child labour should be eradicated (the work-free childhood discourse) and, on the other hand, it is recognised as a right (the regulationist perspective). Based on field studies, the article challenges this dualistic thinking and presents a nuanced, alternative narrative.